2010
DOI: 10.1093/ejo/cjq085
|View full text |Cite
|
Sign up to set email alerts
|

Root resorption associated with ectopically erupting maxillary permanent canines: a computed tomography study

Abstract: The aims of this retrospective computed tomography (CT) study were to determine the occurrence of severe root resorption involving the pulpal canal of adjacent permanent teeth associated with ectopically erupting canines, and to verify the existence of related factors. The sample consisted of 255 consecutive patients (159 females and 96 males, mean age 18.4 and 16.8 years, respectively). Three hundred and thirty-four ectopic maxillary canines and adjacent teeth were analysed using CT images. Statistical signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 21 publications
7
31
2
3
Order By: Relevance
“…This is in line with a study of Ericson and Kurol [17], whereas Cernochova et al [27] found that buccal canines were more frequently related to root resorptions of incisors than palatal canines.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with a study of Ericson and Kurol [17], whereas Cernochova et al [27] found that buccal canines were more frequently related to root resorptions of incisors than palatal canines.…”
Section: Discussionsupporting
confidence: 92%
“…The severity of root resorption was recorded based on the grading systems suggested by Ericson and Kurol. [8]The mesio-distal space available for the canine was assigned to one of three categories, modified from Cernochova et al .,[9] as follows: (A) Lack of space for the erupting canine, (B) complete loss of space, and (C) sufficient space available for the canine.The vertical location of the maxillary canine crown was assigned to one of five categories, modified from Power and Short[10] [Figure 1]. …”
Section: Methodsmentioning
confidence: 99%
“…The mesio-distal space available for the canine was assigned to one of three categories, modified from Cernochova et al .,[9] as follows: (A) Lack of space for the erupting canine, (B) complete loss of space, and (C) sufficient space available for the canine.…”
Section: Methodsmentioning
confidence: 99%
“…[16] In another study of the same type, root resorption of the maxillary lateral incisors was present in 66.7% of the cases and 11.1% of the cases had root resorption of the central incisors. [17] Our results are close to those described in the literature.…”
Section: Discussionmentioning
confidence: 89%